Canva sebagai Media Pembelajaran pada Mata Pelajaran IPA: Seberapa Efektif? Sebuah Studi Literatur - Cindy Paramita Citradevi (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Technological advances are developing so quickly and rapidly that with the new era, many people like to spend time in front of their smartphones. This is what happened to most of our students. Therefore, as educators we can address these problems by making smartphones as partners in learning. Especially now that there are many new websites that provide educational content. One of them is Canva. Canva is a free platform that provides graphic design. The purpose of this literature review is to analyze scientific articles related to the effectiveness of using Canva as a learning medium for students, especially in science subjects. The method used is the literature review method which is sourced from articles in Google Scholar. The scientific articles used in this literature review are within the last 5 years (2018-2022). Then it was analyzed using the PRISMA concept which consisted of 7 points, namely title, abstract, introduction, methods, results, discussions and conclusions. From the 7 articles obtained, 3 of them stated that Canva could improve learning outcomes in science concepts, increase students' motivation and scientific literacy, and is a proper supporting medium in abstract science learning activities because it can provide visualization so that it makes it easier for students to learn.